2021
DOI: 10.1088/1742-5468/abe93f
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental diagram of pedestrian flow including wheelchair users in straight corridors

Abstract: The improvement of evacuation efficiency for pedestrians mixed with wheelchair users has practical significance to public safety. In this study, a series of pedestrian experiments are performed in corridors considering assisted wheelchair users. It is observed that an able-bodied pedestrian’s unimpeded speed and relaxation time are 38.9% higher and 24.5% shorter than those of wheelchair users, respectively. The forward proxemic values of wheelchair users are smaller than their backward ones. However, both are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 39 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…It has been found that the flow is directly proportional to the width of the corridor to some extent [5,9] and that pedestrian speed shows a decreasing trend with increase in pedestrian density. Meanwhile, the dynamics of different groups of pedestrians in corridor flows, such as the elderly [10], children [11] and the disabled [12,13], have attracted the interest of researchers. The speed and flow for elderly and disabled pedestrians are smaller than those for healthy young adults under the same pedestrian density due to their weaker movement abilities, while the specific flow as well as the speed of children is noticeably higher than that of adults at high density.…”
Section: J Stat Mech (2023) 083403mentioning
confidence: 99%
“…It has been found that the flow is directly proportional to the width of the corridor to some extent [5,9] and that pedestrian speed shows a decreasing trend with increase in pedestrian density. Meanwhile, the dynamics of different groups of pedestrians in corridor flows, such as the elderly [10], children [11] and the disabled [12,13], have attracted the interest of researchers. The speed and flow for elderly and disabled pedestrians are smaller than those for healthy young adults under the same pedestrian density due to their weaker movement abilities, while the specific flow as well as the speed of children is noticeably higher than that of adults at high density.…”
Section: J Stat Mech (2023) 083403mentioning
confidence: 99%
“…Therefore, engineering tools (e.g., computational models, simulations, and analytical techniques commonly used in civil and safety engineering disciplines to evaluate and predict the performance of egress systems) lack ecological validity and cannot adequately describe egress performance. Several studies observed reduced flows through bottlenecks and lower pedestrian densities in heterogeneous crowds [10][11][12][13][14][15][16]. A review of egress data considering people with disabilities suggested supplementing pre-movement and horizontal movement data sets considering different types of mobility characteristics [3,17].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is necessary to investigate the distracted behaviors in controlled experimental conditions, which can support the empirical data of pedestrian flow, as well as model development and validation. What's more, the straight corridor is a common geometric structure and widely used for collecting pedestrian movement data [5,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%